STRATEGI KAMPANYE PUBLIC RELATIONS BERBASIS MEDIA SOSIAL DALAM MEMBANGUN BRAND AWARENESS PADA MASYARAKAT DIGITAL - Anggun Larasati; Nuri Anjani; Muhammad Irfan; Sepvi Ananda; Sri Hertimi (Universitas Nahdlatul Ulama Al Ghazali Cilacap, 2026)
The communication paradigm shift in the digital society era demands a reconstruction of the strategic function of Public Relations (PR) from conventional one-way models to an interactive digital ecosystem. A deep investigation into the effectiveness of cross-platform PR campaigns in building brand awareness remains crucial amidst the information overload phenomenon. This study aims to analyze and synthesize social media-based PR campaign strategies in building brand awareness within the digital society. The research method applied is a literature review adopting the Systematic Literature Review (SLR) approach through the PRISMA protocol on 6 reputable scientific articles published between 2016 and 2026. The findings reveal three main pillars for successful digital PR campaigns: (1) the optimization of transmedia storytelling based on interactive visual content; (2) adaptive multi-platform integration tailored to the technical architecture of each media (Instagram, TikTok, and X) to implement symmetrical two-way communication (PR 2.0); and (3) strategic collaboration with digital influencers (particularly micro-influencers) acting as public trust brokers. This study contributes theoretically to the enrichment of cyber PR models and practically provides a strategic framework for practitioners in designing dialogic digital campaigns rooted in the sociological characteristics of contemporary cyber communities.